Departemen Akuntansi Fakultas Ekonomika dan Bisnis Universitas Diponegoro - Rayendra Tegar Baruna; Endang Kiswara (Diponegoro Journal of Accounting, 2026)
This study confronts the predictive power of Altman Z-Score, Springate S-Score, and Zmijewski X-Score across 39 automotive observations on the IDX (2022-2024). Both Friedman and Wilcoxon Tests confirm a significant divergence among the models (Sig. 0.000). Strikingly, Zmijewski reigns superior with an 87.18% accuracy rate, followed by Springate at 82.05%. Conversely, the classic Altman model stumbles at a meager 20.51% due to severe Grey Area constraints. However, for risk-averse investors, Springate and Altman yield a flawless 0% Type I Error. Ultimately, Zmijewski’s emphasis on leverage and liquidity offers the most adaptive diagnostic tool for the automotive sector.